Helicobacter pylori bab characterization in clinical isolates from Bhutan, Myanmar, Nepal and Bangladesh - Ansari, Shamshul (PLoS One, 2017)
BACKGROUND: Helicobacter pylori BabA is an important outer membrane protein that involves in the attachment to the gastric mucosa and enhances the virulence property of the bacterium. This study was aimed to characterize the bab genotypes, to evaluate its association with cagA, vacA and clinical diseases as well as degree of gastric inflammation. METHODS: H. pylori isolates from four countries were subjected for the characterization of bab. The locus specific forward and bab specific reverse primers were used to get the specific products by PCR, which could distinguish the three locus (A, B and C). The histological activities were evaluated according to the Updated Sydney system. RESULT: In patients from high risk countries (Bhutan and Myanmar) relatively higher frequencies of strains with babA-positivity (91.8% and 90.7%, respectively), babA at locus A (98% and 91.2%, respectively) and with single babA (96.8% and 91.2%, respectively) were found. Strains with two loci occupied were the most prevalent in Bhutan (84.6%), Myanmar (74.7%), Nepal (58.3%) and Bangladesh (56.9%). The genotype babA at locus A/babB at locus B/bab-negative at locus C (babA/babB/-) was the most common genotype isolated from Bhutan (82.7%), Myanmar (58.7%), Nepal (32%) and Bangladesh (31.4%) among all genotypes assessed. This genotype was also associated with the peptic ulcer disease (P = 0.013) when compared to gastritis. babA-positive characteristics and the genotype babA/babB/- exhibited the enhanced histological activities. CONCLUSIONS: The higher prevalence of virulence associated babA-positive characteristics and enhanced histological activities in Bhutan than in Myanmar, Nepal and Bangladesh might partly explain why the peoples in Bhutan are at higher risk for developing severe gastric complications.